Upaya Meningkatkan Keterampilan Menulis Deskripsi Melalui Model Picture And Picture pada Siswa Kelas II SD Plus MIP Marelan - Prasasti, Tri Indah; Resti Citra Dewi; Supriadi (JURNAL ARMADA PENDIDIKAN, 2023)
Writing is an important thing as a form of appreciating something and expressing ideas that exist within a person. Writing is an important aspect of learning Indonesian. This research was conducted to improve the ability of grade 2 students at SD Plus MIP Medan in describing a picture in a textbook. This study uses descriptive statistical analysis methods and classroom action research methods. Data collection techniques and data collection tools used were observation, tests, interviews, and documentation. In terms of learning improvement, based on pre-cycle data analysis, learning improvement research can be described using the percentage that achieves KKM sequentially at pre-cycle 46.15%, cycle 1 at 69.23%, and cycle 2 at 100%. Based on the findings in this study, it can be concluded that there is an increase in students' ability to write descriptions using the picture and picture model seen from student learning outcomes from pre-cycle, cycle 1 and cycle 2.